2020
DOI: 10.1021/acs.chemrestox.0c00182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Standardized Medicinal Plant Extracts on Drug Metabolism Mediated by CYP3A4 and CYP2D6 Enzymes

Abstract: The use of medicinal plants concomitantly with conventional drugs can result in herb−drug interactions that cause fluctuations in drug bioavailability and consequent therapeutic failure and/or toxic effects. The CYP superfamily of enzymes plays an important role in herb−drug interactions. Among CYP enzymes, CYP3A4 and CYP2D6 are the most relevant since they metabolize about 50% and 30% of the drugs on the market, respectively. Thus, the main goal of this study was to evaluate the occurrence of in vitro interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 91 publications
1
13
0
1
Order By: Relevance
“…Also, UPLC/DAD showed THEO, NCA, CCA, CGA, CAF, and RUT as the major compounds while UPLC/MS analysis confirmed these compounds and the presence of quinic acid, citric acid, caffeoylglucose, feruloylquinic acid, quercetin-glycoside, and kaempferolrhamnoglucoside. All these data are in agreement with the literature data [18,19,20,31,36]. Considering the high amounts of phenolic compounds detected in I. paraguariensis preparations, the antioxidant activity of these extracts and its chemical markers was also investigated by the DPPH assay.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Also, UPLC/DAD showed THEO, NCA, CCA, CGA, CAF, and RUT as the major compounds while UPLC/MS analysis confirmed these compounds and the presence of quinic acid, citric acid, caffeoylglucose, feruloylquinic acid, quercetin-glycoside, and kaempferolrhamnoglucoside. All these data are in agreement with the literature data [18,19,20,31,36]. Considering the high amounts of phenolic compounds detected in I. paraguariensis preparations, the antioxidant activity of these extracts and its chemical markers was also investigated by the DPPH assay.…”
Section: Discussionsupporting
confidence: 90%
“…Chemical Characterization by LC/MS Analysis. The LC/MS analysis was performed according Feltrin et al [31]. Briefly, the compounds were identified by highperformance liquid chromatography (Waters® Acquity™ UPLC™; catalogue number 186015018) coupled to a photodiode array detector (PDA, Waters®; catalogue number 186015033) and a high-resolution mass spectrometer (Xevo®G2 QTof, WATERS® model; catalogue number 186006532) equipped with a source of electrospray ionization (ESI) operating in positive and negative mode.…”
Section: Chemical Characterizationmentioning
confidence: 99%
“…While most phytochemical studies focused on identifying and isolating flavonoids, other components that have gained less attention are worth mentioning in this review. For instance, the iridoids geniposide 1 and 2 were found in the leaves of C. pachystachya and C. hololeuca [49] and the flavonolignans ent-mururin A and entvaccinin A in the leaves of C. obtusifolia [61]; the coumarins 4-ethyl-5-(n-3valeroil)-6-hexahy-drocoumarin, scopoletin [4,59], some organic acids, anthraquinones, and 1 alkaloid were also found in Cecropia species (Table 4S, Supporting Information) [59,62,63].…”
Section: Other Constituentsmentioning
confidence: 99%
“…The results also showed that the butanol fraction and its main constituents isoorientin, orientin, isovitexin, catechin, epicatechin, and procyanidin B2, B3, B5, and C1 had equal potency inhibiting gastric H+, K+ ATPase enzyme activity, when tested both individually and in a complex mixture (Table 5S, Supporting Information) [20]. Feltrin et al showed that a standardized extract of this plant was able to inhibit 2 cytochrome P450 enzymes, namely CYP3A4 and CYPD6 (Table 5S, Supporting Information), a characteristic that may modify the bioavailability and efficacy of certain drugs [62].…”
Section: Other Biological Effectsmentioning
confidence: 99%
“…Interaktionen mit Medikamenten sind nicht bekannt [22], mit Coumarinderivaten aber möglich (es sollte engmaschig kontrolliert werden). In vitro interagiert der Artischocken-Wirkstoff mit CYP3A4 und CYP2D6 [10].…”
Section: Interaktionenunclassified